Evaluation of herbaceous cotton lines and cultivars in the Northeast of Brazil. I. Yield - Santana, João Cecílio Farias de; Santos, Elton Oliveira dos; Neto, Miguel Barreiro; Crisóstomo, João Ribeiro; Calvacanti, Fernando Bezerra; Costa, Joaquim Nunes da; Gomes, Ivan Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Some upland cotton (Gossypium hirsutum L.r. latifolium Hutch.) lines developed by the Centro Nacional de Pesquisa de Algodão (CNPA) were tested together with cultivars developed by CNPA and by other research institutions in the country. Seed cotton yield was studied utilizing data from the regional cotton variety tests. Seeds were planted in a complete randomized block design with nine treatments and eight replications. The test was conducted at 21 different localities of Northeast of Brazil, in 30 experiments in the period of two years: 1980/81 and 1981/82- The cultivar BR 1 and lines CNPA 77-149, CNPA 77-150 and CNPA 76-6873 had the highest seed cotton yield; the last one was the most productive with an average of 1,457 kg/ha in 21 out of the 30 experiments, surpassing the two control varieties BR 1 and IAC 17 by 8% and 15%, respectively.